Assessment and classification of different ashes from waste incinerators in Thailand - Raji Muthuraja; Chatpong Na Pombhejara; Sunantha Ganesan; Chodchanok Attaphong; Nattaya Morawan; Juckrit Vicheanteab; Dao Janjaroen (Results in Engineering, 2024)
• The characteristics of different types of fly ash in Thailand were studied • The particle size of fly ashes from waste incinerators was larger (16.4 – 45.6 μm) than ready-mixed concrete fly ash (2.13 – 21.2 μm). • MFA1, MFA2, IFA and CFA1 were identified as hazardous wastes. • Ash samples showed notable levels of PCDD with only 13.0–25.7% and 0.7–6.8% dioxins found in boiler slag and flue gas, respectively Rapid urbanisation and a growing population have led to a huge production of solid waste worldwide. To mitigate solid wastes, Thailand adapts incineration. As a consequence, a variety of fly ashes being produced in large quantities. Fly ash management is therefore a risk for the future. A comparison of the chemical and physical properties of five sources of ashes from the waste incinerators in three regions in Thailand, namely MFA1, MFA2, IFA, and fly ash that used in a ready-mixed concrete plant, CFA1 and CFA2 was conducted. Additionally, bottom ashes, MBA1, MBA2 and IBA were also characterized similarly. The analysis showed that coal fly ash from ready mixed concrete plant of CFA1 and CFA2 were classified under class F and C, respectively. The heavy metal analysis showed that fly ash from MFA1 and IFA has high amount of Zn (7,523 mg/kg and 28,315 mg/kg), followed by MFA1 has high amount of cadmium (127 mg/kg) and MFA1 and IFA showed high concentration of lead (1,955 mg/kg and 1,425 mg/kg). The present study show that fly ash often contains heavy metals, dioxins, and other hazardous substances, highlighting the need for detailed analysis to determine proper handling and disposal methods. Advanced classification systems, which may include parameters such as leaching behavior, particle size distribution, and contaminant concentrations, are essential for categorizing fly ash into appropriate management pathways, such as landfilling, resource recovery, or reuse in construction materials.
Keywords: Recycling and utilization of industrial and municipal waste in materials production; Healthcare and Environmental Waste Management; Municipal Solid Waste Management